Application of the revised WHO causality assessment protocol for adverse events following immunization in India. Issue 33 (24th July 2017) - Singh, Awnish Kumar; Wagner, Abram L.; Joshi, Jyoti; Carlson, Bradley F.; Aneja, Satinder; Boulton, Matthew L.
Abstract: Background: In 2013, the World Health Organization (WHO) and CIOMS introduced a revised Causality Assessment Protocol (CAP) for Adverse Events following Immunization (AEFI). India is one of the first countries to adopt the revised CAP. This study describes the application of the revised CAP in India. Methods: We describe use of CAP by India's AEFI surveillance program to assess reported AEFIs. Using publicly available results of causality assessment for reported AEFIs, we describe the results by demographic characteristics and review the trends for the results of the causality assessment. Results: A total of 771 reports of AEFI between January 2012 and January 2015, completed causality review by August 2016. The cases were reported as belonging to a cluster (54%; n = 302), hospitalized or requiring hospitalization (41%; n = 270), death (25%; n = 195), or resulting in disability (0.4%; n = 3). The most common combinations of vaccines leading to report of an AEFI were DTwP, Hepatitis B, and OPV (14%; n = 106), followed by Pentavalent and OPV (13%; n = 103), and JE vaccine (13%; n = 101). Using the WHO Algorithm, most AEFI reports (89%, n = 683) were classifiable. Classifiable AEFI reports included those with a consistent causal association (53%; n = 407), an inconsistent causal association (29%; n = 226) or were indeterminate causal association with implicated vaccine(s) or vaccination process (6.5%; n = 50) (Fig. 1); 88 reports remained unclassifiable. Conclusions: The revised CAP was informative and useful in classifying most of the reviewed AEFIs in India. Unclassifiable reports could be minimized with more complete information from health records. Improvements in causality assessment, and standardization in reporting between countries, can improve public confidence in vaccine system performance and identify important vaccine safety signals.